2020
DOI: 10.36483/vanvetj.646976
|View full text |Cite
|
Sign up to set email alerts
|

Toksoplazmozisli Koyunlarda Oksidatif Stres ve Seruloplazmin Düzeylerinin Belirlenmesi

Abstract: The aim of the study was to determine the oxidative stress parameters as well as ceruloplasmin levels in sheep with toxoplasmosis. In order to investigate biochemical parameters, a total of 30 sheep were used in the study. According to ELISA test results, 20 sheep were infected with toxoplasmosis, while 10 healthy sheep sera had antibodies negative. Biochemical analysis included total oxidant capacity (TOC), total antioxidant capacity (TAC), oxidative stress index (OSI), nitric oxide (NO) and ceruloplasmin lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Ceruloplasmin has functions such as increasing various enzyme (cytochrome C oxidase and Cu-Zn superoxide dismutase) activities with copper, providing higher antimicrobial power in phagocytic cells and protecting against oxidative damage (Bayyit and Merhan, 2020). moreover, ceruloplasmin is an indicator of the presence of infection (Bozukluhan et al, 2016;Bayyit and Merhan, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ceruloplasmin has functions such as increasing various enzyme (cytochrome C oxidase and Cu-Zn superoxide dismutase) activities with copper, providing higher antimicrobial power in phagocytic cells and protecting against oxidative damage (Bayyit and Merhan, 2020). moreover, ceruloplasmin is an indicator of the presence of infection (Bozukluhan et al, 2016;Bayyit and Merhan, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Ceruloplasmin, which is involved in the antioxidant system, is a moderately important acute phase protein in addition to its functions such as protecting cells against oxidative damage and antimicrobial activity (Bozukluhan et al, 2020). Bozukluhan et al, (2020) reported that the value of ceruloplasmin was found to be high in sheep with toxoplasmosis, but this was statistically insigni cant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Araştırmacılar (3,5,20) göbek kordonundaki enfeksiyon etkenlerinin portal ven aracılığı ile eklem gibi daha uzak yapılara yayılarak artrit başta olmak üzere çeşitli sekonder hastalıklar oluşturduğunu ve omfaloflebitis vakalarının %50 sinden fazlasında en sık gözlenen komplikasyonun septik artritis olduğunu bildirmişlerdir (5,18). Sunulan bu çalışmada topallık problemi ile getirilen buzağıların klinik muayeneleri neticesinde göbek bölgesi lezyonu gösteren (omfalitis, omfaloflebitis, omfaloarteritis) 64 olguda 29 adet (%45.31) monoartrit ve 12 adet (%18.75) poliartrit olmak üzere toplam 41 artritli (% 64.06) buzağı tespit edildi.…”
Section: Tartişma Ve Sonuçunclassified